Peningkatan Seal Online Player Loyalty: Peran Experiental Value, Promosi, dan Player Satisfaction (Seal Online Gladius) - Bayu Adhi Nugroho; Andriya Risdwiyanto (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
Information technology (IT) plays an important role in supporting various aspects of modern life and industry. This research used quantitative methods with purposive sampling technique for sampling. Respondents were taken from members of the Seal Online Gladius community in an application called Discord totaling 298 members with a sample of 58 respondents. The research results showed that the contribution of the independent variable influence to the dependent variable was 13.8%, while partially the experiential value and the promotion did not have a significant effect on players’ loyalty. However, the player satisfaction has a significant effect on their loyalty.